Selected Intrapersonal Traits as Predictors of Stress Management among Principals in Public Secondary Schools in Kenya - (:unkn) unknown (JOOUST, 2017)
Secondary school principals worldwide have reported experience of stress and their reaction to srress can be categorized as behavioral, psychological or physiological. In Homa Bay County secondary school principals have reported stressful experiences. Stress response by secondary school principals in Homa Bay County depends on their expectations, experience, personality, beliefs, resources, values and drives and their responses to stress can sometimes be very detrimental to their mental and physical health thus impacting negatively on their work output as principals. The purpose of the study was to investigate selected intrapersonal variables as predictors of stress management among secondary school principals in Homa Bay County. The study objectives were: to establish the relationship between Type A personality trait and stress management among secondary school principals in Homa Bay County, to determine the relationship between Type B personality trait and stress management among secondary school principals in Homa Bay County, to examine the relationship between locus of control and stress management among secondary school principals in Homa Bay County and to find out the relationship between self-efficacy and stress management among secondary school principals in Homa Bay County. Kelly’s personal construct theory supported by Carl Rogers Person Centred theory informed the study. The study adopted a Convergent Parallel research design within the Mixed Method approach. From a population of 295 principals, the study used Krejcie and Morgan's (1970) table to select 169 principals to be included in the study. Stratified random sampling was used to cater for the different categories of secondary schools and proportionate simple random sampling was used to sample the secondary principals who were included in the study. Purposive sampling was used to sample the two (2) national schools in the County. Quantitative data was collected using a set of questionnaires while an interview schedule was used to collect qualitative data from twenty (20) principals. Validity of the research instrument was ensured through expert judgement by the University lecturers. The reliability of the research instruments was determined by the use of Cronbach's Alpha and a co-efficient(r= 0.814) was obtained. The quantitative data was analyzed using Statistical Package for Social Sciences (SPSS) windows version 22 by use of statistical tests such as Pearson's Product Moment Correlation Coefficient and Analysis of Variance (ANOVA), while qualitative data was analyzed using thematic analysis. The study established a negative (r= -337) relationship between personality type "A" personality trait and stress management. On Type B" personality trait the study established a positive relationship between Type B personality trait and stress management (r= .620). The ANOVA results indicated that there was a statistically significant difference (p=.05) in stress management scores for locus of control [F (2, 165) =356.7, p<.05]. Internal locus of control exhibited higher (M=3.37 and SD=.29) stress management than the other two groups of locus of control, with effect size of .0812. The study also noted that there was a moderate positive (r=.412) but highly significant (p<.05) relationship between self• efficacy and stress management. Qualitative results revealed that most principals used multi• zasking to manage and accomplish their tasks thus reducing their stress. It is envisaged that thrs study would provide valuable information to the secondary school principals on how to - ercome stressful situations within their schools. It was concluded that intrapersonal traits secondary school principals to mitigate stressful situations. The study recommends that the stry of Education should induct newly appointed principals on how to enhance their nal traits; this would help them understand how to manage stressful situations in their SG:.OO!s The study suggests that a further research be conducted on Personal, intrapersonal and occupational factors influencing occupational stress amongst primary schools heads in Kenya.
Keywords: Intrapersonal traits.; Stress Management among Principals.; Public Secondary Schools in Kenya; Kenya.